378 Salpingectomy at the time of hysterectomy for benign gynaecologic disease: a comparison of surgical approaches. (18th September 2019) - Obermair, H; Borg, E
Abstract : Objectives: Due to a growing body of evidence demonstrating the involvement of the fallopian tubes in serous ovarian malignancies, prophylactic salpingectomy has been recommended to be discussed with or offered to patients undergoing hysterectomy for benign indications. This study aimed to compare rates of bilateral salpingectomy at the time of hysterectomy for benign indications across different surgical approaches. Methods: This study was performed through a retrospective review of data collected for clinical audit via SurgicalPerformance, a web-based audit project which collects data from individual surgeons. Of 11477 hysterectomy records available, 6608 were eligible for analysis. Results: During hysterectomy, salpingectomy was performed in in 3856 of 6608 cases (58%) overall. Based on surgical approach, salpingectomy occurred in 65% of cases using an open approach, 70% with laparoscopic approach, 78% with laparoscopic assisted vaginal hysterectomy, 73% with robotic, 73% with conversion to open and 13% with vaginal. There was a significant difference in the rates of salpingectomy during vaginal hysterectomy compared to other approaches (p≤0.001). When adnexal surgery was performed at the time of hysterectomy, those under the age of 50 more frequently underwent salpingectomy alone, whereas those over the age of 50 more frequently underwent bilateral salpingo-oophrectomy. Conclusions: Salpingectomy at the time of hysterectomy for benign indication occurred significantly less frequently when the operation occurred using a vaginal approach, compared to other approaches. While the data presented here are hypothesis generating, they justify further prospective research into barriers to salpingectomy when a vaginal hysterectomy approach is performed.